Cancer immunogenic cell death via pyroptosis with CXCR4-targeted nanotoxins in hepatocellular carcinoma - Huang, Yingbin; Li, Yihu; He, Rui; Dong, Shuyi; Zhao, Zheng; Jiao, Xingyuan (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction Cytotoxic agents have shown limited benefits in hepatocellular carcinoma (HCC), mediated in part by the lack of targeting. As cell-penetrating peptides (CPPs) are capable of delivering various biologically active molecules into cells, including protein, peptides, small chemo-drugs, and nucleic acid with or without targeting, we developed T22-PE24, a CXCR4-targeted self-assembling cytotoxic nanotoxin, to effectively induce HCC pyroptosis. Methods T22 incorporating enhanced green fluorescent protein (EGFP) or PE24 was purified from DE3 bacterial cells and characterized using transmission electron microscopy, the Zetasizer Nano®, and SEC-HPLC. The internalization effect of T22-EGFP was detected by flow cytometry system (FCS) in CXCR4+/LM3(CXCR4−) HCC cells. The CCK8, lactate dehydrogenase (LDH) release, Western blot, and nude mice HCC models were used to estimate the cell viability of T22-PE24. The complete-immunity HCC tumor-bearing mice model was used to assess the immune response of T22-PE24. Results The round shape under transmission electron microscopy, 49.4 nm hydrodynamic diameter, and −33.33 mV zeta potential indicated that T22-PE24 self-assembled into nanoparticles. T22 incorporating EGFP selectively internalized in CXCR4+ HCC cells and showed no accumulation in CXCR4-knockout HCC cells. The T22-PE24 nanotoxin induced HCC pyroptosis via the caspase-3/GSDME signaling pathway and suppressed tumor growth in the absence of histological alterations in normal organs. Using the complete-immunity HCC tumor-bearing mice model, we found that T22-PE24 nanotoxin effectively induces the global reprogramming of cell components of the immune tumor microenvironment, leading to enhanced antitumor effects compared to those observed in immunodeficient mice. Conclusion Our findings demonstrate the activation of the innate immune response in HCC by inducing pyroptosis with T22-PE24 nanotoxin treatment and support an implementation of this strategy for HCC treatment.